The Effectiveness of Motivational Council (MI Model) on Prediction of the Relapse in Women Addicted to Narcotic Drugs - S Dehghani Firozabadi; H Ghasemi; R Montazer Hadash; M Fatehizadeh; S Zolfaghari; A.A Ebrahimi (Drug Control Headquarters, Research and Education Office, 2014)
Objective: The aim of present research was to study of the effectiveness of motivational council on preventing of relapse in women addicted to narcotic drugs. Method: This research was carried on by semi experimental method with the pretest-posttest with witness group. Population included all addicted women referring to Ayandeh Roshan recovery addiction camp of Isfahan during summer 1391. Sample was 30 women who were selected of addicted women of recovery camp, and randomly divided to two groups. The aware of returning to use of narcotic drugs questionnaire administered among two groups two times as pretest and posttest. The motivational counsel training administered for 8 sessions in experimental group. Results: The results showed that motivational counsel training was affected on experimental group. Conclusion: It could be said that motivational council was useful and effective in reducing the relapse of using narcotic drugs.